2018
DOI: 10.3390/ma11020287
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensing Applications of ZnO Nanomaterials

Abstract: Recent advancement in nanoscience and nanotechnology has witnessed numerous triumphs of zinc oxide (ZnO) nanomaterials due to their various exotic and multifunctional properties and wide applications. As a remarkable and functional material, ZnO has attracted extensive scientific and technological attention, as it combines different properties such as high specific surface area, biocompatibility, electrochemical activities, chemical and photochemical stability, high-electron communicating features, non-toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(72 citation statements)
references
References 107 publications
0
71
0
1
Order By: Relevance
“…In this regard, thin films of TiO 2 and ZnO build-up with the sputtering technique can also be considered as sensorial layers. These films proved to be efficient for the detection of molecules with phenolic rings and they presented high mechanical stability under pH fluctuations [36][37][38]. This study aimed to achieve a customized e-tongue device to follow real-time degradation and quantification of TCS and its derivative by-products in an electrochemical flow reactor (EFR) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, thin films of TiO 2 and ZnO build-up with the sputtering technique can also be considered as sensorial layers. These films proved to be efficient for the detection of molecules with phenolic rings and they presented high mechanical stability under pH fluctuations [36][37][38]. This study aimed to achieve a customized e-tongue device to follow real-time degradation and quantification of TCS and its derivative by-products in an electrochemical flow reactor (EFR) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9]. Article a II-VI semiconductor, are among the most important semiconductor nanomaterials as they possess wide-band gap (3.37 eV at room temperature), high-exciton binding energy (60 meV) and visible optical transmittance (above 80%), thermal and chemical stability, non-toxicity, and so on [10][11][12][13]. Because of their significant use in electronics, sensors (gas, chemical and bio), optical devices, photocatalysis, energy devices (solar cells, supercapacitors, batteries, hydrogen energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that the co-presence of hierarchical ZnO nanostructures and noble metal nanoparticles can be advantageous for many applications (i.e., catalytic/photocatalytic, electric charge capacity, and sensing property) [22,23], due to the strong surface plasmon resonance and to the charge separation efficiency given by the noble metal nanoparticles. Further study is needed for the knowledge of the process that is occurring in the vapor-solid process and of the role of Au/Pt nanoparticles in affecting the shape and size of ZnO particles, as well as their effectiveness in increasing quantities and homogeneity of the samples.…”
Section: Morphology From Sem and Afm Imagesmentioning
confidence: 99%